KONSTRUKSI SOSIAL MODERASI BERAGAMA BERBASIS KEARIFAN LOKAL: STUDI KUALITATIF PADA MASYARAKAT MULTIRELIGIUS DI KABUPATEN BALANGAN - Abdullah Abdullah (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to analyze the social construction of religious moderation based on local wisdom among multireligious communities in Balangan Regency. The main issue examined is how communities construct, interpret, and practice religious moderation within a social life characterized by religious and cultural diversity. This research employed a qualitative approach with a case study design. Data were collected through semi-structured interviews, observation, and documentation. Informants were selected using purposive and snowball sampling, involving religious leaders, traditional leaders, village government officials, representatives of the Religious Harmony Forum or the Ministry of Religious Affairs, youth, and residents from different religious backgrounds, with particular attention to Kapul Village, Halong District, as one example of a multireligious community. The findings reveal that religious moderation is constructed through four main themes: the practice of peaceful coexistence, local wisdom as social cohesion, the role of religious and traditional leaders, and the internalization of moderation values through family and social environments. These findings indicate that religious moderation is not merely a normative concept, but a socio-cultural practice shaped through shared lived experiences. This study contributes to the development of the sociology of religion and provides practical implications for strengthening religious harmony policies based on local wisdom.